مشروع ربط البحار الخمسة ومتغيرات النظام الدولي - حيدر, عفيف; اسماعيل, عصام; ميليش, فريد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
طرحت سورية عبر مواقف متتابعة مشروع ربط البحار الخمسة: المتوسط والأسود وقزوين والخليج العربي والبحر الأحمر، سياسياً واقتصادياً واجتماعياً لتوحيد جهود دولها, وتحقيق مصالحها, وبالتالي مواجهة المشروع الصهيوني الذي يعمل على تفتيت المنطقة. وهو مشروع طموح وناجح بكل المقاييس حيث يعمل على تأسيس تاريخ جديد في المنطقة لكنه تعرض لنكسة وفق المعطيات الدولية والإقليمية الراهنة, وأن ما يحصل منذ سنوات في منطقتنا عامة وفي سورية خاصةً كونها في موقع القلب للمشروع هو نتيجة لصراع الإرادات بين مشاريع الهيمنة والسيطرة من جهة و نهج سورية القائم على القراءة الدقيقة والموضوعية لمجمل المتغيرات الدولية والإقليمية من جهة أخرى, وبأن هناك إمكانية تجدد المشروع وفق آليات جديدة في المستقبل بالاستناد الى العلاقات السورية الايرانية العراقية.Syria raised through successive positions of linking the five seas: the Mediterranean, Black and Caspian and the Arabian Gulf and the Red Sea project, politically, economically and socially to unite its efforts and pursue their interests, and thus face of the Zionist project, which works to break up the region.It is an ambitious project and successful by all standards where it's works to establish a new history in the region, but suffered a setback in accordance with the current international and regional data, and that what is happening for years in our region in general and in Syria as especially being in the heart of the project is the result of a conflict of wills between the hegemony projects and control on the one hand and Syria approach based on accurate and objective reading of the entire international changes and Regional the other hand, and that there is a possibility of renewed project in accordance with the new mechanisms in the future based on the Iraqi-Syrian-Iranian relations.